Protective effects of curcumin on epileptic rodent models by alleviating oxidative stress and inflammation: a meta-analysis and mechanism exploration - Dai, Peng; Xu, Lingyu; Zhang, Peng; Liang, Zheng; Chu, Yunhang; Yu, Ziqiao; Cao, Lin; Sun, Peng; Li, Xia (Frontiers in Pharmacology, 2025)
ObjectiveThe purpose of this study is to systematically evaluate the therapeutic effect of curcumin on rodent epilepsy models through a meta-analysis of multiple animal experiments. It will also explore its potential mechanism of anti-oxidative stress and anti-inflammation to provide a theoretical basis for the application of curcumin in the clinical treatment of epilepsy.MethodsA total of 23 eligible animal studies were identified by searching eight databases (up to March 2025), including PubMed, Embase, Web of Science, Cochrane Library, and CNKI, Wan Fang, VIP, CBM. SYRCLE’s risk of bias tool was used to assess the quality of the literature, and Meta-analysis was performed using Review Manager 5.4 and Stata 18 software. Primary outcome measures included epilepsy latency, Morris water maze escape latency, oxidative stress markers (MDA, GSH, SOD), inflammatory factors (IL-1β, TNF-α), and Glial fibrillary acidic protein (GFAP).ResultsMeta-analysis showed that the curcumin intervention group significantly extended the epilepsy latency (SMD = 1.85, 95% CI = 1.05–2.64, P < 0.00001) and shortened the water maze escape latency (SMD = −1.69, 95% CI = −2.23–1.16, P < 0.00001). In terms of antioxidant indicators, curcumin significantly decreased MDA levels (SMD = −3.50, P < 0.00001) and increased GSH (SMD = 2.87, P < 0.00001) and SOD (SMD = 2.42, P < 0.00001). The anti-inflammatory results showed that the levels of IL-1β (SMD = −1.73, P = 0.04) and TNF-α (SMD = −1.65, P < 0.00001) were significantly decreased, and the levels of GFAP-positive cells were decreased (SMD = −1.72, P = 0.05). Subgroup analysis showed that medium and high doses (100–299 mg/kg and ≥300 mg/kg) of curcumin were more stable, but the low dose group (<100 mg/kg) did not conduct in-depth analysis due to insufficient sample size of individual indicators. Sensitivity analysis and funnel plots suggest robust results, but some publication bias exists.ConclusionCurcumin can effectively improve epileptic seizures and cognitive dysfunction in epileptic rodents through the dual mechanisms of antioxidative stress (inhibiting lipid peroxidation and enhancing antioxidant enzyme activity) and anti-inflammatory (reducing the release of pro-inflammatory factors and inhibiting glial cell activation). However, species differences and potential publication bias have certain effects on the results, and high-quality clinical studies can be carried out in the future to verify their clinical application value.